2004
DOI: 10.1080/10412905.2004.9698698
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Seasonal Variations of Spike Lavender Oil from Southern Spain

Abstract: The composition of six essential oil samples, obtained by steam distillation of twigs of spike lavender (Lavandula latifolia Med.) harvested in three different locations from southern Spain during the full flowering and fruiting phenological stages, has been analyzed by capillary GC and GC/MS in combination with retention indices. Yields of the oils during flowering (1.5-2.2%) were 2.5-7 times higher than during fruiting (0.3-0.6%). Among the 56 identified constituents (accounting for 96.0-97.5% of the oils), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…Salido et al (2004) reported a similar result, suggesting that acylation activity in lavandin is of L. angustifolia origin. (+)-borneol is oxidized by 2 electrons of the hydroxyl group with borneol dehydrogenase and converts to (+)-camphor in Saliva officinalis (Croteau and Karp, 1976).…”
supporting
confidence: 68%
“…Salido et al (2004) reported a similar result, suggesting that acylation activity in lavandin is of L. angustifolia origin. (+)-borneol is oxidized by 2 electrons of the hydroxyl group with borneol dehydrogenase and converts to (+)-camphor in Saliva officinalis (Croteau and Karp, 1976).…”
supporting
confidence: 68%
“…It is well known that the variability in the spike lavender oil composition is primarily genotype dependent (Harborne and Williams, 2002); thus, the variability in monoterpene content among the spike lavender plants analyzed reflects the bulked seed origin of the plants used as a source of explants for transformation. It is worth noting that the most common compounds found in the oils from transgenic and control spike lavender oils, namely, a-and b-pinene, cineole, camphor, linalool, a-terpineol, and borneol, were within the ranges observed in other studies on chemical composition of spike lavender oils (Asociación Españ ola de Normalizació n y Certificació n, 1997; Harborne and Williams, 2002;Salido et al, 2004). As already suggested (Dudareva et al, 2004), we found that the formation of volatile compounds in spike lavender is spatially regulated, with flowers producing the most diverse and the highest amount of these compounds.…”
Section: Discussionmentioning
confidence: 72%
“…Chemical classes represented in the species include phenolics (Areias et al 2000) and terpenes (Salido et al 2004;Aburjai et al 2005). Tiliacos et al (2008) determined that a substantial component of Lavandula intermedia is made up of two compounds, coumarin and herniarin (7-methoxycoumarin).…”
Section: Introductionmentioning
confidence: 99%